Intravenous iron monotherapy for the treatment of non-iron-deficiency anemia in cancer patients undergoing chemotherapy: a pilot study - Abdel-Razeq H; Abbasi S; Saadi I; Jaber R; Abdulelah H (Dove Medical Press, 2013)
Hikmat Abdel-Razeq,1 Salah Abbasi,1 Iyad Saadi,1 Rana Jaber,2 Hazem Abdelelah1 1Department of Internal Medicine, 2Department of Pharmacy, King Hussein Cancer Center, Amman, Jordan Background: Anemia in patients with cancer who are undergoing active therapy is commonly encountered and may worsen quality of life in these patients. The effect of blood transfusion is often temporary and may be associated with serious adverse events. Erythropoiesis-stimulating agents are not effective in 30%–50% of patients and may have a negative effect on overall survival. Aims: To assess the efficacy and feasibility of intravenous iron therapy in patients with cancer who have non-iron-deficiency anemia and who are undergoing treatment with chemotherapy without the use of erythropoiesis-stimulating agents. Methods: Adult patients with solid cancers and non-iron-deficiency anemia were included. Ferric sucrose at a dose of 200 mg was given in short intravenous infusions weekly for a total of 12 weeks. Hemoglobin level was measured at baseline, every 3 weeks, and 2 weeks after the last iron infusion (week 14). Adverse events related to intravenous iron were prospectively reported. Results: Of 25 patients included, 19 (76.0%) completed at least three iron infusions and 14 (56.0%) finished the planned 12 weeks of therapy. The mean hemoglobin level of the 25 patients at baseline was 9.6 g/dL (median, 9.9 g/dL; range, 6.9 g/dL10.9 g/dL). The mean change in hemoglobin level for the 15 patients who completed at least 9 treatments was 1.7 g/dL (median, 1.1 g/dL; range, −1.9 g/dL to 3.2 g/dL); it reached 2.1 g/dL (median, 1.3 g/dL; range, −0.2 g/dL to 4.6 g/dL; P = 0.0007) for the 14 patients who completed all 12 weekly treatments. Five (20.0%) patients were transfused and considered as treatment failures. No treatment-related adverse events were reported. Conclusion: Intravenous iron treatment alone is safe and may reduce blood transfusion requirements and improve hemoglobin level in patients with cancer who are undergoing anticancer therapy. Further randomized studies are needed to confirm these findings. Keywords: anemia, cancer, chemotherapy, intravenous iron, transfusion